Characterization of Thermoplastic Elastomers Made of MAH-g-EPDM and ZnO Using Liquid-State NMR - Kwon1, Hyuk-Min; Kim1, Yeowool; Choi1, Sung-Seen; Woo Bae2, Jong; Kim2, Jung-Soo (Asian Journal of Chemistry, 2013)
Thermoplastic elastomers made of maleic anhydride-grafted ethylene-propylene-diene terpolymer (MAH-g-EPDM) and zinc oxide were characterized by liquid-state nuclear magnetic resonance spectroscopy. Organic materials remained in the samples were extracted and dried for nuclear magnetic resonance analysis. The samples were soaked in benzene and were put into a nuclear magnetic resonance tube. Sufficient deuterated chloroform was then added to the nuclear magnetic resonance tube. The 1H and 13C NMR spectra showed the characteristic peaks for the ethylene, propylene and diene units of ethylene-propylene-diene terpolymer. Raw and cured ethylene-propylene-diene terpolymers were also analyzed and the results were compared with the thermoplastic elastomers. The analytical results suggested that the outside parts of MAH-g-EPDM did not participate in the formation of ionomers between the maleic acid groups of MAH-g-EPDM and zinc oxide. The outer parts might be composed of ethylene-propylene sequences and non-modified dienes not including maleic anhydride and maleic acid groups.